2020
DOI: 10.1186/s12882-020-02179-9
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiosis in glomerular disease patients with immunosuppressive therapy

Abstract: Background Glomerular disease patients have a high risk of infection, which contributes to the progression of disease per se and mortality, especially in those with long-term use of glucocorticoids and (or) immunosuppressive agents. Cases of sporadic nocardiosis have been reported in glomerular disease patients, and this observation was conducted to comprehensively understand the manifestations of and treatments for nocardiosis, which is commonly misdiagnosed as pneumonia or tuberculosis or eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…In our study, nodule/mass and consolidations were the major radiologic manifestations in NS patients with Nocardia infections, consistent with the previous single-center review ( Guo et al., 2020 ; Han et al., 2020 ). A retrospective study of Cushing’s syndrome with nocardiosis reported that cavitary lesions and nodules were the most common radiological findings ( Zhang et al., 2021 ), indicating that the main radiologic manifestations may have slight differences in different diseases.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, nodule/mass and consolidations were the major radiologic manifestations in NS patients with Nocardia infections, consistent with the previous single-center review ( Guo et al., 2020 ; Han et al., 2020 ). A retrospective study of Cushing’s syndrome with nocardiosis reported that cavitary lesions and nodules were the most common radiological findings ( Zhang et al., 2021 ), indicating that the main radiologic manifestations may have slight differences in different diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Han et al. ( Han et al., 2020 ) proposed that pulmonary abscesses were important signs of nocardiosis in glomerular disease patients, whereas only 4 patients (case 2, 4, 25, 27) presented with pulmonary abscesses in our review. Therefore, further studies with more cases are needed to assess if pulmonary abscesses were important characteristics in NS patients and the radiological differences between NS patients and other nocardiosis.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Although Nocardia spp. are opportunistic bacteria related to kidney disease and hypertension in humans [ 35 ], the association between high BP and a high Nocardia abundance was addressed, for the first time, by our study.…”
Section: Discussionmentioning
confidence: 95%